Keseimbangan Ion Pada Koagulasi Protein Ampas Tahu - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2003)
Protein coagulation is one of the important steps in solid protein production. These products are usually used in food industries as functional ingredients add,...d to the food in order to emulsify, to form foams or gels, to bind water, to control color etc. Due to the amphoteric properties of the protein molecules, protein solubility is very influenced by pH. The purpose of this experiment was to obtain a mathematical model which can be used to determine the effect of pH on protein solubility. Because the ionic equilibrium constants are influenced by temperature, this study also includes the effect of temperature. Soybean curd waste was used to test the model. The process took place in an extraction flask provided with stirrer and the pH was fixed at a certain value. The temperature of the solution was kept constant at the desired value using a waterbath. The experiment was carried out for 45 minutes and equilibrium was assumed to be achieved. The precipitate was then filtered. The protein contents in the filtrate were analyzed using UV/Visible spectrofotometer accurding to Lowry method. Compared with the experimental data, the model can qualitatively predict the solubility of protein and quantitatively predicts the isoelectric point.